2017
DOI: 10.1038/ajg.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Barrett’s Esophagus is Rare Following Endoscopic Eradication Therapy Coupled With Effective Reflux Control

Abstract: The current study highlights the importance of reflux control in patients with BE undergoing EET. In this setting, EET has long-term durability with low recurrence rates providing early evidence for extending endoscopic surveillance intervals after EET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 57 publications
1
53
1
1
Order By: Relevance
“…None of the three studies that defined CRIM on two negative endoscopies6–8 evaluated the variation in the incidence of recurrence over time across all grades of dysplasia. In one single-centre study, 20% of patients had NDBE at baseline and no recurrences were reported after 3 years, implying little benefit from surveillance beyond 3 years post-CRIM 6. This is in contrast to data from our study in which we estimated the recurrence rate to remain constant, or at least not decrease by more than 7% for every doubling of follow-up time throughout the study period that extended beyond 3 years.…”
Section: Discussioncontrasting
confidence: 96%
“…None of the three studies that defined CRIM on two negative endoscopies6–8 evaluated the variation in the incidence of recurrence over time across all grades of dysplasia. In one single-centre study, 20% of patients had NDBE at baseline and no recurrences were reported after 3 years, implying little benefit from surveillance beyond 3 years post-CRIM 6. This is in contrast to data from our study in which we estimated the recurrence rate to remain constant, or at least not decrease by more than 7% for every doubling of follow-up time throughout the study period that extended beyond 3 years.…”
Section: Discussioncontrasting
confidence: 96%
“…14,22,41 Most patients achieve CE-IM within 3 ablative therapy sessions. 53,54 Esophagectomy is considered as the treatment of choice for patients with submucosal cancer (T1b sm2-3 disease), poorly differentiated cancer, and cancer associated with lymphatic or vascular infiltration given the high risk of lymph node metastasis (at least 20%). 2,23,55 Long-term survival data in patients undergoing EET using contemporary treatment modalities and identification of stage T1b EAC patients who may be able to undergo EET and achieve comparable outcomes with esophagectomy should be addressed in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although the temporality of recurrence after achieving CE-IM cannot be established with the available reports, recent reports suggest that most recurrences are reported within the first 3 years after achieving CE-IM. 53,54 A limited number of studies report on the risk factors associated with recurrence (ongoing reflux and presence of erosive esophagitis, older age, nonwhite race, smoking, obesity, pretreatment BE length, number of EET sessions), and these associations need to be explored and confirmed in future studies. 51,53,54,[64][65][66] Surveillance intervals suggested by current guidelines are largely driven by expert opinion and low quality evidence.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta‐analysis identified PPI use associated with a 71% risk reduction of EAC and HGD in BE patients, supporting the role of acid reduction to reduce cancer risk . Furthermore, it has been recently proposed that an effective reflux control is associated with a statistical significant reduction in BE recurrence after RFA . Optimizing the PPI dose or receiving fundoplication was correlated with a low rate of BE recurrence after RFA.…”
Section: Treatmentmentioning
confidence: 94%
“…79,80 Furthermore, it has been recently proposed that an effective reflux control is associated with a statistical significant reduction in BE recurrence after RFA. 81 Optimizing the PPI dose or receiving fundoplication was correlated with a low rate of BE recurrence after RFA. Some studies suggest that fundoplication may result in improved control of gastroesophageal reflux (acid, weakly acid, and weakly alkaline) 82 and is associated with fewer recurrences of intestinal metaplasia after RFA in selected patients with a coexisting hiatal hernia of > 3 cm 83 or more severe reflux exposure.…”
Section: Endoscopic Therapy For Bementioning
confidence: 94%